2022
DOI: 10.1111/rda.14172
|View full text |Cite
|
Sign up to set email alerts
|

Male SIRT1 insufficiency leads to sperm with decreased ability to hyperactivate and fertilize

Abstract: Sperm physiology is mainly affected by the functions of testis and, during spermatogenesis, sperm are provided of proteins driving posterior motility (Björkgren & Sipilä, 2019). For example, NAD +dependent histone deacetylases (Sirtuins) need to be expressed in testes for proper sperm motility (Coussens et al., 2008). Moreover, spermatozoa are transcriptionally and translationally silent, therefore the ability to acquire fertilization competence, i.e. support capacitation and hyperactivation, depends on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…SIRT1 and SIRT3 proteins are found in seminal plasma, and their levels in seminal plasma are inversely correlated with oxidative stress biomarkers and the amount of sperm DNA fragmentation, as evident in our study. These findings are in agreement with the previously published reports [31,32,104,105]. Seminal plasma provides nutrients for the maintenance of the maturing sperms, and the increased generation of ROS could result in reduced sperm metabolism and diminish motility, thus leading to infertility [106,107].…”
Section: Discussionsupporting
confidence: 93%
“…SIRT1 and SIRT3 proteins are found in seminal plasma, and their levels in seminal plasma are inversely correlated with oxidative stress biomarkers and the amount of sperm DNA fragmentation, as evident in our study. These findings are in agreement with the previously published reports [31,32,104,105]. Seminal plasma provides nutrients for the maintenance of the maturing sperms, and the increased generation of ROS could result in reduced sperm metabolism and diminish motility, thus leading to infertility [106,107].…”
Section: Discussionsupporting
confidence: 93%
“… 876 In addition, to investigate SIRT1 regarding adjuvant strategies in the treatment of male infertility, dysregulation of SIRT1 and mitochondrial SIRT (SIRT3-5) genes were associated with human male infertility. 921 , 922 In female genital system disease, a limited number of studies have paid attention to polycystic ovary syndrome (PCOS) and endometriosis. PCOS patients had higher SIRT1 levels than healthy controls 923 and involvement of the SIRT1/AMPK axis in autophagy activation in PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of previous research have demonstrated that SIRT1 reduction leads to mitochondrial dysfunction by increasing ROS, LPO, and DNA damage in sperm, resulting in decreased sperm fertilization ability [48]. Similarly, studies by Cuerda et al have shown that insufficient SIRT1 function in men leads to overactivation of sperm and decreased fertilization ability [49]. Thus, SIRT1 expression was significantly positively correlated with sperm concentration, total motility, and normal sperm morphology.…”
Section: Discussionmentioning
confidence: 83%